Organizational implementation of investment controlling mechanism performance. (Economics and region, 2016)
Basic principles of enterprise investment controlling are analyzed in the article. The importance of level of investment activity, industrial enterprise identity and the role that management assigns to investment controlling in the overall organizational structure of the company are emphasized as critical parameters in the process of investment controlling function composition. Functions that confer on responsible for investment controlling on each step of conducting of investment projects are mentioned. The importance of interoperability between investment controller and other departments at each stage of the investment process is emphasized. Peculiarities of investment controlling implementation regarding ecological and social projects are presented. Practical recommendations on formalizing the role of individual departments in the investment projects implementation are given. It is mentioned that such formalization should be reflected in the internal procedures of the company and ultimately lead to streamlining investment activities, precise planning of investment budgets and accurate cash flows forecast while investment projects execution.
Keywords: controlling; investment controlling; controlling mechanism; investments; organizational structure; cash flow